Contextual Learning Based on Multicultural Increase Students’ Knowledge Competence in Civic Education - Sudira, Ni Made Lyvia Komalasari; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2020)
Civic education that has not been able to give meaning to students results in the need for innovation in learning. Learning can be realized by applying contextual learning based on multiculturalism. This research is a quasi-research with nonequivalent control group design. The population in this study amounted to 130 students, while the sample in this study amounted to 44 students taken using the Cluster Random Sampling technique. The collection in this study was a multiple-choice objective test instrument of 32 questions. Based on the analysis of the polled variance t-test obtained t-count = 3.83> t-table = 1.68 at a significance level of 5% with dk = 42, which means that H0 is rejected and Ha is accepted. This proves that there are significant differences in the competence of civic knowledge between groups of students who are taught with the Multicultural Contextual learning model and students who are taught by conventional learning. So, it can be concluded that Multicultural-based Contextual learning has a significant effect on the civic knowledge competence of elementary students. The implication of this research is through the application of Multicultural-based Contextual learning students can easily interpret the learning that is done.